Historical blocking: KZ 2022-01-04 (Kazakhstan) - Voidly (2022)
WARNING severity censorship detected in Kazakhstan. Confidence: 77%. Data sourced from ooni-historical-backfill.
Censorship Incident ID: KZ-2022-0009
Keywords: censorship; KZ; censorship; warning